Validation of a Gamified Circular Design Methodology through a Design Workshop - Ramadan, Menatalla M.A.M.; Gabr, Aly H. (International Journal of Architectural Engineering Technology, 2025)
This research integrates theory with practice (thought and action) connecting real-life problems to theorical foundations, with the dual aim of solving a design problem in the circular economy (CE) and delivering new knowledge through experimentation. This paper stems from the observation that architects commonly rely on their personal experience while designing without adopting structured frameworks. The present study aims at validating a previously proposed circular design methodological framework in practice. To achieve this aim, the research employed a design workshop to test this design methodology. This is followed by an analysis of how non-expert architects in CE perceived and applied it. The study recorded participants’ interaction with the gamification sense implied in the methodology and assessed their ability to develop designs compatible with CE principles. Data collection included sketches, video recordings, observations, and written notes. The findings highlight the potential of the circular design methodology to support the design process in CE. Participants reported positive experiences, describing the methodology as flexible, easy to comprehend, enjoyable, time-efficient, and educational. The results validate the applicability of this circular design methodology, leading to setting a step-by-step guideline for its future implementation. Ultimately, the validation of this design methodology may promote wider dissemination and acceleration of the culture of circular design in architectural practices, even for non-expert architects in CE.